An experimental, video-based investigation into the motivating impact of choice and positive feedback among students with different motor competence levels. (3rd July 2020) - De Meester, An; Van Duyse, Femke; Aelterman, Nathalie; De Muynck, Gert-Jan; Haerens, Leen
ABSTRACT: Background: Research stemming from Self-Determination Theory (SDT) shows that physical education (PE) teachers who endorse an autonomy-supportive and structuring motivating style positively affect students' motivation, engagement and learning. Choice provision and positive feedback are two concrete strategies that are part of an autonomy-supportive and structuring style, respectively. While the benefits of choice provision and positive feedback have been shown in contexts other than PE, evidence in the specific context of PE is much scarcer. Grounded in SDT and relying on experimental design, the present study sought to examine the effects of choice provision and positive feedback on students' motivational experiences in PE, and whether these effects were moderated by students' actual motor competence (AMC). Method: A sample of 277 students (41% boys, M age = 12.78 years) was randomly assigned to one of four experimental conditions (2 × 2 design). Prior to the experimental manipulation, participants' AMC was measured with the Test of Gross Motor Development second edition. Participants then watched a videotaped PE lesson, in which the provision of choice (choice – no choice) and type of feedback (corrective feedback – positive and corrective feedback) were manipulated. Participants were asked to imagine how they would feel being a student in the displayed lessons. After watching the video, they completed validated questionnaires on their (1) anticipated need satisfaction and frustration and (2) autonomous and controlled motivation. MANOVAs were conducted to investigate the differences between the experimental groups in terms of anticipated need satisfaction, need frustration and motivation. Multiple linear regression analyses were used to examine the potential moderating role of AMC. Findings and conclusions: The benefits of choice provision were clearly shown with students in the choice condition anticipating significantly more autonomy, competence and relatedness satisfaction and autonomous motivation, while they anticipated significantly less autonomy and relatedness frustration when compared to students in the no choice condition. Similarly, the addition of positive feedback to corrective feedback yielded clear benefits, with lower averages in anticipated need frustration found among students who watched the videos in which positive feedback was added to corrective feedback. No support was provided for a synergetic motivational effect between choice and positive feedback. Overall, the present findings show the importance of offering choice and providing positive feedback to motivate students in PE, with positive effects being present for all students independent of their initial AMC levels. Although few interaction effects were found, lowly motor competent students benefited even more from receiving positive feedback than highly motor competent students. The findings of this study are important to take into account in PE teacher education programs and professional training programs for PE teachers about how to teach in a (more) motivating way.